Nile Red and 2-NBDG Are Incompatible for the Simultaneous Detection of Lipid and Glucose Accumulation. (22nd December 2016) - Hogan, Andrew M.; Swaminathan, Viswanathan; Pallegar, Nikitha K.; Christian, Sherri L.
Abstract : Glucose is the universal energy source and a critical substrate for lipid synthesis in mammalian cells. Analysis of both glucose and lipid in cells is important for the understanding of the regulation of lipid synthesis in many cell types, but especially adipocytes, the major storage cell for fat in mammals. The fluorescent 7-nitrobenz-2-oxa-1, 3-diazole (NBD) derivative of glucose, 2-NBDG, is used to monitor glucose uptake and the lipid-selective fluorophore Nile red is used to monitor lipid accumulation. Previous reports have used NBD-based fluorophores and Nile red simultaneously despite the possibility of spectral overlap. In this study, we determined if these fluorophores were experimentally compatible in preadipocytes and adipocytes stained with 2-NBDG and Nile red separately or costained. We found that Nile red is detectable in the wavelengths necessary to excite and detect 2-NBDG. This interference was further increased by the solvatochromic effect of lipid-localized Nile red. In addition, we found a synergistic increase in fluorescent intensity when both fluorophores were present. Unfortunately, even fine control of the excitation or emission wavelengths did not identify wavelengths suitable for selective detection when cells were costained. Therefore, 2-NBDG and Nile red cannot be used simultaneously—but can likely be used sequentially—to assess glucose uptake and lipid accumulation in lipid-laden cells.